Context-Specific Osteogenic Potential of Mesenchymal Stem Cells - Aleksandra Kostina; Arseniy Lobov; Daria Semenova; Artem Kiselev; Polina Klausen; Anna Malashicheva (Biomedicines, 2021)
Despite the great progress in the field of bone tissue regeneration, the early initiating mechanisms of osteogenic differentiation are not well understood. Cells capable of osteogenic transformation vary from mesenchymal stem cells of various origins to mural cells of vessels. The mechanisms of pathological calcification are thought to be similar to those of bone formation. Notch signaling has been shown to play an important role in osteogenic differentiation, as well as in pathological calcification. Nevertheless, despite its known tissue- and context-specificity, the information about its role in the osteogenic differentiation of different cells is still limited. We compared mesenchymal stem cells from adipogenic tissue (MSCs) and interstitial cells from the aortic valve (VICs) by their ability to undergo Notch-dependent osteogenic differentiation. We showed differences between the two types of cells in their ability to activate the expression of proosteogenic genes RUNX2, BMP2, BMP4, DLX2, BGLAP, SPRY, IBSP, and SPP1 in response to Notch activation. Untargeted metabolomic profiling also confirms differences between MSCs and VICs in their osteogenic state. Analysis of the activity of RUNX2 and SPP1 promoters shows fine-tuned dose-dependency in response to Notch induction and suggests a direct link between the level of Notch activation, and the proostogenic gene expression and corresponding osteogenic induction. Our data suggest that osteogenic differentiation is a context-dependent process and the outcome of it could be cell-type dependent.